2021
DOI: 10.1016/j.esmoop.2020.100045
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling in non-small-cell lung cancer in young patients. A systematic review

Abstract: Lung cancer in young patients is an uncommon and understudied entity that harbors distinctive epidemiological, clinic-demographic, and genomic features. We carried out a systematic review of genomic profiling in young patients with lung cancer from 2010 to 2020 in the main electronic databases and selected 23 manuscripts. Lung cancer in young patients occurs more frequently in women with adenocarcinoma histology and at more advanced stages. Some studies report higher oncogenic genomic alteration in this popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 74 publications
(263 reference statements)
1
12
0
Order By: Relevance
“…The overall ALK rearrangement rate (2.6%) in this large retrospective data set was within the range observed previously in other non-selected populations [13][14][15]. Likewise, the younger age of the patients whose cancers harbored the ALK translocation has been reported by other groups as well [16,17]. It is not surprising that, of those young patients with advanced lung cancer, there would be an enriched population of ALK positive patients and that was confirmed in the evaluation of this dataset.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall ALK rearrangement rate (2.6%) in this large retrospective data set was within the range observed previously in other non-selected populations [13][14][15]. Likewise, the younger age of the patients whose cancers harbored the ALK translocation has been reported by other groups as well [16,17]. It is not surprising that, of those young patients with advanced lung cancer, there would be an enriched population of ALK positive patients and that was confirmed in the evaluation of this dataset.…”
Section: Discussionsupporting
confidence: 88%
“…As such, we examined histology and smoking status within this patient cohort. Regardless of documented histology, a higher ALK rearrangement rate (8.9%) was observed among patients who had no smoking history compared to patients with a smoking history (1.5% ALK positivity) which represent the largest number of patients in this cohort (17,003). Analyzing patients in this study by their histology, we observed that patients with nonsquamous histology had an ALK rearrangement rate of 3%, patients in the NSCLC NOS category (most likely poorly differentiated adenocarcinomas and squamous cell carcinomas) 1.9%, and patients with squamous histology 0.8%.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have investigated the potential genetic profiles of early-onset lung cancer, which also revealed that adenocarcinoma was the most prevalent subtype of early-onset lung cancer among young women. 36 As for males, our results indicated that the decreasing trend in incidence was much more significant among the young than the old. And one recent study has shown that the decreasing trend was appreciably larger in the young men than the old men in Europe.…”
Section: Discussionmentioning
confidence: 53%
“…Secondly, clinical misdiagnosis, according to the low incidence of lung cancer in young patients, may further delay the cancer diagnosis of this subset of patients (6). Finally, lung cancer with earlier disease onset may present a distinct disease entity with more aggressive disease biology (8,18). As such, Li et al recommend that age 45 may be the optimal screening cut-off for initiating lung cancer screening (19), with the aim of earlier detection and treatment of young lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%